Online social support for cancer caregivers: alignment between requests and offers on CaringBridge. Issue 1 (2nd January 2021) - Bloom, Rosaleen Duggan; Reblin, Maija; Chou, Wen-Ying Sylvia; Beck, Susan L.; Wilson, Andrew; Ellington, Lee
Abstract: Objectives: Exploring CaringBridge, we describe types of social support caregivers requested, types of social support offered, and the alignment between the two. Research approach: A retrospective, longitudinal, descriptive approach. Sample: Twenty public CaringBridge sites. Methodological approach: The Social Support Behavior Code system was adapted and applied to cancer-caregiver journal entries ( n = 389) and guestbook posts ( n = 2, 466) to identify types of support (emotional, esteem, informational, network, tangible, and no support requested/offered). Matches between requests and offers were examined. Findings: Cancer caregivers requested different types of support from their guests, most commonly emotional support. However, in most posts, caregivers did not request any support ( n = 238, 61.18%). Guests offered all support types, but predominately offered emotional support ( n = 2, 353, 95%). When support was requested, 66.67% of requests received a matched offer within 24 hours. Interpretation: Social media platforms may provide all types of support to caregivers.